Menguak Realitas Pertanggungjawaban Pidana dalam Kasus Kecelakaan Lalu Lintas yang Mengakibatkan Korban Meninggal Dunia - Abdaud, Faisal (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
Traffic accidents resulting in fatalities are categorized as serious traffic accidents. The purpose of this study is to analyze the reality of criminal liability in cases of traffic accidents resulting in fatalities where the victim's family and the perpetrator's family agree to settle. This study uses a normative legal research type. This qualitative study uses a legislative approach, conceptual approach, and case approach. The results of the study show that the traffic accident case involving the perpetrator and victim "NA" is classified as a serious traffic accident resulting in fatalities as stipulated in Article 229 paragraph (4) of the UULLAJ. According to the provisions in the UULLAJ, there is no clause that allows serious traffic accident cases to be settled amicably. The provision of material compensation to the heirs of "NA" in the form of medical and/or funeral expenses is an obligation as stipulated in Article 235 paragraph (1) of the UULLAJ without waiving the criminal charges, so the provision of compensation is a form of responsibility that can be taken into consideration as a mitigating factor by the judge in court.